Hubungan Antara Kepemimpinan Melayani Dan Kepribadian Dengan Kinerja Pegawai - Raden Muhammad Syakur Fathurrahman; Sri Sundari; Marisi Pakpahan (Journal of Management and Social Sciences, 2024)
The performance of human resources can be influenced by the conditions of servant leadership that are formed. Factors that influence employee performance in servant leadership include a lack of commitment from employees towards understanding the values ​​and rules that have been established, a lack of disciplined behavior, a lack of inheritance of servant leadership, and a lack of understanding organizational identity. These things cause service leadership to be less than optimal in achieving the stated vision and mission of the organization. One factor in good servant leadership is that it requires commitment from all members of the organization under the leadership of someone who is able to influence all members of the organization and is expected to be able to build good and strong servant leadership. survey research design with a correlational approach. The approach used is a quantitative approach as the basis for analysis. There is a positive, very significant and strong relationship between servant leadership and employee performance. There is a positive, very significant and strong relationship between Personality and Employee Performance. There is a positive, very significant and strong relationship between Servant Leadership (X1) and Personality (X2) together with Employee Performance (Y). The two go hand in hand, which means that the higher the Service Leadership and Personality together, the higher the Employee Performance.